Finnish multiple sclerosis patients treated with cladribine tablets: a nationwide registry study - Rauma Ilkka; Viitala Matias; Kuusisto Hanna; Atula Sari; Sipilä Jussi OT; Ryytty Mervi; Soilu-Hänninen Merja; Järvinen Elina (Elsevier BV, 2025)
BACKROUND
Cladribine tablets for adult patients with highly active relapsing multiple sclerosis (MS) have been available in Finland since 2018. Real-world data from different genetic and geographical backgrounds are needed to complement data from clinical trials.
METHODS
We investigated the use of cladribine tablets in Finland in a non-interventional cohort study, based on real-world data from the nationwide Finnish MS registry. All eligible patients who had initiated treatment with cladribine tablets in 2018-2020 were included. Descriptive analyses for outcomes were conducted using summary statistics. Time-dependent endpoints were analyzed using cumulated events analysis based on 1-Kaplan-Meier estimates and curves. Subgroups were analyzed separately according to the number of previous disease-modifying therapies (DMTs) and the most common last preceding therapies.
RESULTS
Data of 179 patients were analyzed. Median follow-up time was 19.0 months (interquartile range [IQR] 12.0-26.2). Of the 134 patients who were followed for at least 12 months, 112 patients (83.6%) remained relapse-free during follow-up. Mean annualized relapse rate (ARR) was 1.0 (standard deviation [SD] 0.89) at baseline, and 0.1 (SD 0.30) at follow-up. Patients with two or more previous DMTs had shorter time to first relapse (median 2.5 months, IQR 0.6-9.3) when compared to patients with 0-1 previous DMTs (median 11.4 months, IQR 8.7-13.1) (p=0.013). After excluding patients switching from fingolimod (n=33), a statistically significant difference in time to first relapse was no longer observed between the two groups (p=0.252). Adverse events (AEs) were reported in 30 patients (16.8%). The most frequent AE was headache (n=14, 7.8%). One patient (0.6%) died of cardiac arrest. Discontinuation of cladribine tablets was reported in nine patients (5.0%).
CONCLUSION
The mean ARR observed in this cohort was similar to what has been reported in clinical trials. Approximately half of the patients had used two or more previous DMTs before cladribine tablets. These patients had a shorter time to first relapse when compared to patients with 0-1 previous DMTs, mostly driven by early relapses in patients switching from fingolimod.